Ecological Influences on Coastal Finfish Recruitment: FA239, 5/2022 - Love, Gabrielle; Braswell, Anna; Collins, Angela B.; Camp, Edward (EDIS, 2022)
Florida is experiencing many human and climate-related changes to the aquatic environment that can affect fish. Lost or altered habitat, for instance, can lead to changes in fish populations that may impact survival, growth, or recruitment of those populations. Recruitment influences how many adult fish are later available for spawning and continuing the population. Understanding recruitment and how it is affected by ecological influences is important for considering the potential effects of ongoing climate change, as well as restoration and management of water quality and habitat. This publication provides background information useful to anyone interested in understanding more about factors affecting fish populations and should be especially useful to Extension agents and management agency personnel who would like an overview of these topics before engaging with stakeholders.